SVM based pattern recognised islanding detection approach in a multiple distributed generation system - Srinivasa Rao, Gundala; Kesava Rao, G. (International Journal of Engineering and Technology, 2018)
The penetration of Distributed generation (DG) ensures the increase of demand for consistent, reasonable and spotless electricity facing with some design and operational challenges such as islanding. Several active and passive methods have been suggested in the past to detect islanding. Since they suffer from the large non detection zone and a high cost. In order to defeat such issues we propose a SVM based pattern recognising approach for islanding detection in a multiple DG system. The results show that our proposed method detects islanding with high accuracy.